The Diversification of Products for Empowerment Women’s Keliling Benteng Ulu Village, Martapura Barat Subdistrict, Banjar District - Isnaini; Asnawati; Yuliani, Rahma; Riyani, Risma Yulfa; ‘Ibaadurrahmaan, Khansa Khafiya; Ariady, Nabilla Azzahra (PT FORMOSA CENDEKIA GLOBAL, 2024)
In 2023, the PKK women's group in Keliling Benteng Ulu Village, West Martapura District, Banjar Regency has started producing instant herbal drinks with the herbal name